2015
DOI: 10.1128/jvi.01324-15
|View full text |Cite
|
Sign up to set email alerts
|

Simian Varicella Virus Is Present in Macrophages, Dendritic Cells, and T Cells in Lymph Nodes of Rhesus Macaques after Experimental Reactivation

Abstract: Like varicella-zoster virus (VZV), simian varicella virus (SVV) reactivates to produce zoster. In the present study, 5 rhesus macaques were inoculated intrabronchially with SVV, and 5 months later, 4 monkeys were immunosuppressed; 1 monkey was not immunosuppressed but was subjected to the stress of transportation. In 4 monkeys, a zoster rash developed 7 to 12 weeks after immunosuppression, and a rash also developed in the monkey that was not immunosuppressed. Analysis at 24 to 48 h after zoster revealed SVV an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 27 publications
3
28
0
Order By: Relevance
“…Isotype control did not reveal any staining (data not shown). Consistent with our earlier observations (30), SVV antigens colocalized more often in macrophages than in any other cells, and no SVV antigens were detected in lymph nodes from latently infected or SVV-seronegative monkeys. SVV antigen was found in multiple lymph nodes in all monkeys, only some of which were associated with areas of rash.…”
Section: Monkeysupporting
confidence: 92%
See 2 more Smart Citations
“…Isotype control did not reveal any staining (data not shown). Consistent with our earlier observations (30), SVV antigens colocalized more often in macrophages than in any other cells, and no SVV antigens were detected in lymph nodes from latently infected or SVV-seronegative monkeys. SVV antigen was found in multiple lymph nodes in all monkeys, only some of which were associated with areas of rash.…”
Section: Monkeysupporting
confidence: 92%
“…4E). Although SVV antigens were detected in the lungs from all monkeys (data not shown), similar to our earlier observations (30), the number of antigen-positive cells in lungs was substantially less than in lymph nodes. SVV glycoproteins gH and gL were detected mostly in the cytoplasm of neurons and, less frequently, in nonneuronal cells in thoracic ganglia from monkey JF07 (Fig.…”
Section: Monkeysupporting
confidence: 89%
See 1 more Smart Citation
“…We previously showed that this model recapitulates the essential features of VZV infection in humans including varicella and establishment of latency in sensory ganglia (Messaoudi et al , 2009). Moreover, as described for VZV, SVV reactivates under conditions of immune suppression (Mahalingam et al , 2010; Mahalingam et al , 2007b; Ouwendijk et al , 2013; Traina-Dorge et al , 2015). To investigate the role that T cell senescence plays in SVV reactivation, rhesus macaques latently infected with SVV were first thymectomized and then depleted of either CD4 or CD8 T cells.…”
Section: Introductionmentioning
confidence: 99%
“…Next, we evaluated histology of dorsal root ganglia from rhesus macaques after simian varicella virus (SVV), a DNA virus related to human varicella zoster virus, reactivation as previously described. (19) We found increased levels of pS129 asyn in 15 dorsal root ganglion from SVV-infected rhesus macaques compared to seronegative control rhesus macaques ( Fig. 4D-F).…”
Section: Hsv1-infected Asyn Wt and Komentioning
confidence: 67%